Does Pioglitazone Lead to Neutrophil Extracellular Traps Formation in Chronic Granulomatous Disease Patients? - Hule, Gouri P.; Bargir, Umair Ahmed; Kulkarni, Manasi; Kambli, Priyanka; Taur, Prasad; Desai, Mukesh; Madkaikar, Manisha Rajan (Frontiers in Immunology, 2019)
Nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase, enzyme complex responsible for Reactive oxygen species (ROS) production is defective in chronic granulomatous disease (CGD) patients. This enzyme helps in antimicrobial host defence by phagocytes. CGD patients have inability to form Neutrophil extracellular traps (NETs), which are composed of granule derived proteins from neutrophils decorated with decondensed chromatin. Mitochondria has gained attention, being a rich source of flavochrome enzymes due to presence of several sites for superoxide production. Recently, PPARγ agonists, a mitochondrial ROS inducer induces mitochondrial ROS formation post treatment in murine NADPH oxidase knockout models. Mitochondrial ROS is also essential for NOX independent NETosis. Our study for the first time detects induction of NETosis independent of NADPH oxidase post treatment with agonists such as pioglitazone and rosiglitazone in CGD subjects. Neutrophils isolated from CGD subjects were treated with pioglitazone and rosiglitazone. After treatment, qualitative analysis of NET formation was done using confocal microscopy after staining with DAPI. Quantitative estimation of extracellular DNA was performed using Sytox green. Mitochondrial ROS production with PPARγ agonist treated/untreated neutrophils was detected using MitoSOX red. Pioglitazone and Rosiglitazone induces significant NET formation in CGD patients. Our data clearly signifies effect of PPARγ agonists in induction of NET formation in CGD cases. Apart from the proposed experimental studies regarding the detailed mechanism of action controlled trials could provide valuable information regarding the clinical use of Pioglitazone in CGD patients as Curative HSCT remains challenging in developing countries.